Selected Factors Related to Sleep Duration in Preterm Infant after Discharge from Hospital - คำอุเทน, ชฎารัตน์; จีระแพทย์, วีณา (Journal of The Royal Thai Army Nurses, 2019)
The research was to examine the sleep duration of preterm infants after discharge and the relationship between the intrinsic factors (sex, gestational age and type of milk) and the extrinsic factors (maternal stress, mother-neonate relationship, family income and mothers’ education level). Subjects consisted of 130 pairs of mothers and their preterm infants with gestational ages of 28 to 35 weeks and first time admitted to the hospital. They were selected by using multistage random sampling. Research instruments included questionnaires of mothers’ and preterm neonates’ personal factors, sleep log form, maternal stress questionnaire, mother-neonate relationship questionnaire. Data ware analyzed by Pearson’s product moment correlation coefficient and Chi-square test. Research findings were as follows: The sleep duration of preterm infant was inadequate f significantly correlation with the sleep duration of preterm infant (χ2 = 15.405, 12.438 and 15.123, p <.01, respectively), gestational age and mother-neonate relationship were significantly positive correlation with the sleep duration of preterm infant (r = .491 and .265 , p< .01 respectively) and maternal stress was significantly negative with the sleep duration of preterm infants (r = -.364, p<.01) Research results suggest knowledge for nursing practice in premature infant discharge preparation for the mother. Nurses can promote preterm infants adequate sleep duration after discharge home by promoting mother-neonate relationship and preparing mother for managing stress especially for lactation performance.